2013
DOI: 10.1155/2013/626452
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Surface Modification of Hydroxyapatite

Abstract: The purpose of this study was to establish an acid-etching procedure for altering the Ca/P ratio of the nanostructured surface of hydroxyapatite (HAP) by using surface chemical and morphological analyses (XPS, XRD, SEM, surface roughness, and wettability) and to evaluate the in vitro response of osteoblast-like cells (MC3T3-E1 cells) to the modified surfaces. This study utilized HAP and HAP treated with 10%, 20%, 30%, 40%, 50%, or 60% phosphoric acid solution for 10 minutes at 25°C, followed by rinsing 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Contact angle depends on many factors, for instance, surface roughness, surface chemistry, and grain size. 27 Because nHA is more hydrophilic as an inorganic material than PEEK, and the nHA/ PEEK composite is rougher than PEEK, the improvement in hydrophilicity seen with the nHA/PEEK composite may stem from changes in the surface roughness and chemistry, 27,28 which may have affected the functions of the osteoblasts in this study.…”
mentioning
confidence: 93%
“…Contact angle depends on many factors, for instance, surface roughness, surface chemistry, and grain size. 27 Because nHA is more hydrophilic as an inorganic material than PEEK, and the nHA/ PEEK composite is rougher than PEEK, the improvement in hydrophilicity seen with the nHA/PEEK composite may stem from changes in the surface roughness and chemistry, 27,28 which may have affected the functions of the osteoblasts in this study.…”
mentioning
confidence: 93%
“…Therefore, we hypothesized that an acid-etching procedure with phosphoric acid could be used to alter the Ca/P ratio of the HAP surface directly in order to achieve a bioactive surface that best mimics the initial phases proposed by Bertazzo et al [7]. In our previous study, we found that the Ca/P ratio of a nanostructured HAP surface could be effectively altered using a 30% phosphoric acid-etching process, which was further found to enhance the initial adhesion, proliferation, and differentiation of MC3T3-E1 cells [10].…”
Section: Introductionmentioning
confidence: 76%
“…The HAP plates were treated with 30% phosphoric acid [H 3 PO 4 ] (lot no. T1949; Sigma-Aldrich Japan; Tokyo, Japan) solution for 10 minutes at 25˚C, followed by rinsing 3 times with ultrapure water (MilliQ water: >18 MΩcm) to achieve the modified HAP surface, HAP-30% PA [10]. The surface characteristics of HAP-30% PA were then compared to the untreated HAP surface as a control using the methods described below.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations